AI-Powered Mediated Synchronous Corrective Feedback on Efl Senior High School Students’ Paragraph Writing Skill - Sumedi, Siti Hanna (EDULIA: English Education, Linguistic and Art Journal, 2024)
This study investigated the effect of AI-powered mediated Synchronous Corrective Feedback as an AI-based automated pedagogical aid on senior high school students’ English writing skill. Correspondingly, this study was conducted through quantitative methods, specifically quasi-experimental research design. There were 30 eleventh-grade students as research subjects who were assigned into two different classes. Practically, 15 students were sorted to an experimental class in which implemented AI-powered mediated Synchronous Corrective Feedback supported by the teacher’ corrective feedback in terms of track changes, recast and metalinguistic feedback. On the other hand, the rest of 15 students were assigned into a control class that personally applied AI-powered mediated Corrective Feedback. This study revealed there was a significant effect of AI-powered mediated Synchronous Corrective Feedback implemented in experimental class on students’ paragraph writing score. Students in the experimental class significantly performed better in writing English paragraphs and obtained higher scores in the English paragraph writing test compared to students in the control class. Therefore, this study concluded AI-powered mediated Synchronous Corrective Feedback along with support, presence, and assistance of teachers in the matter of immediate and synchronous feedback was totally remarkable and crucial as it effectively and successfully improved students’ writing skill and mastery in English Paragraph Writing. Keywords: Artificial Intelligence, Corrective Feedback, Writing Skill